A survey on the Journal of EAHIL: results and considerations (Journal of EAHIL, 2015)
A survey addressed to Journal of EAHIL readers was carried out in December 2014 - January 2015. The aim was to gather opinions and ideas and, on the basis of the results, to further develop JEAHIL to better serve the needs of all EAHIL members. We got 109 answers with lots of ideas and feedback. It was a pleasure to see how appreciated the Journal is, both as a tool for sharing information and as a way to create sense of community. The critical comments were few, but equally valuable. So thank you all the respondents for your contribution!